Proceedings of the Conference on Finite Groups - Scott, William R. (William Raymond), 1919-; Gross, Fletcher (Academic Press, Inc., 1976)
This volume consists of the papers presented at a conference on finite groups which took place in Park City, Utah on February 10-13, 1975. The subjects discussed at the conference were in one of the five main areas of finite group theory, including characterizing simple groups, representations of simple groups, representations and characters of finite groups, permutation groups, and group theory.